KELAYAKAN PERANGKAT PEMBELAJARAN BAHASA INDONESIA BUATAN GURU MTS SWASTA PONTIANAK PADA MASA PANDEMI COVID-19 - Khairullah, Khairullah; Priyadi, Antonius Totok; Martono, Martono (Universitas Tanjungpura, 2021)
ABSTRACT This study examined the feasibility of Indonesian learning tools made by teachers of private MTs Pontianak at the times of covid-19 pamdemic. Based on the results of the study, the teacher already made several good learning tools,however there were still Â shortcomings in certain components. The method used was descriptive qualitative research. The results of the study showed that the tools made by teachers of private MTs Pontianak that were good, there were lesson plan, teaching materials, learning media and evaluations (the questions made by teachers). However there will still some improvement needed in several components of the learning tools, such as school units, the core activity that were still the same from the first until the final meeting, and also the assessment rubric. Nevertheless, this study will alleviate teachers to prepare learning tools for the use of school accreditation, achieving school's vision and mission in the academic field and improving the quality of education in school.Â Keywords : Indonesian, Pontianak, The Feasibility of Learning Tools Â